Benzylation of acetic acid to benzyl acetate over highly active and reusable micro/meso-HZSM-5 - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Raut, Sunil A.; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
Catalytic benzylation of acetic acid (AA) with benzyl alcohol (BA) to benzyl acetate was studied over zeolites viz. H-ZSM-5 (microporous, medium pore), Micro/Meso-HZSM-5 (combination of micro- and meso pore), H-Beta (microporous, large pore) to investigate catalytic activity and selectivity towards benzyl acetate. Micro/Meso-HZSM-5 obtained by desilication post-treatment has been employed as a heterogeneous catalyst for benzylation reaction probably for the first time. Micro/Meso-HZSM-5 was found to be a promising catalyst for benzylation with AA conversion of 94%, selectivity towards benzyl acetate of 95%. The detailed optimization of process parameters such as molar ratio, catalyst loading, reaction temperature and time was also presented. Micro/Meso-HZSM-5 catalyst was observed to be stable for six cycles (1 fresh and 5 recycles). The first order reaction kinetics (R-2 >0.98) indicated that reaction rate constants increased with increasing reaction temperature. The activation energy for benzylation of AA with BA over Micro/Meso-HZSM-5 was obtained to be 15.07 kJ mol(-1), which is far less than the reported. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acetic acid; Benzyl acetate; Benzyl alcohol; Benzylation; Micro/Meso-HZSM-5; Reaction kinetics